Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Multiple Intelligences dalam Pembelajaran Kurikulum Merdeka - Nurdianah, Lutfiyan (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Every student inherently possesses multiple intelligences across various types, though some are more developed than others. The current independent curriculum grants freedom to schools, teachers, and students to maximize their respective competencies. A challenge in the learning process is that many teachers in Indonesia do not yet understand the appropriate methods to highlight the strengths of each student's intelligence. Due to this lack of understanding regarding the implementation of multiple intelligences, teachers are not able to optimally develop each student's unique intelligences. This research aims to develop a product in the form of student worksheets (in Bahasa called LKPD) based on multiple intelligences within the independent curriculum, which is suitable for use in elementary schools. The research methodology adapts the Borg & Gall R&D method but only utilizes seven stages: data collection, planning, product draft development, field testing, product revision, final product, and dissemination. Based on the research findings, the multiple intelligences-based LKPD meets the criteria of being valid, practical, and effective, making it suitable for use in science education at the fourth-grade level of elementary school. This multiple intelligences-based LKPD can interpret various multiple intelligences, thereby optimizing the talents, interests, and intelligences of each individual character, which in turn will impact the overall quality of education.